Warriors : Navajo code talkers - Kawano, Kenji, 1949- (Flagstaff, Ariz. : Northland Pub. Co., 1990)
During World War II, as the Japanese were breaking American codes as quickly as they could be devised, a small group of Navajo Indian Marines provided their country with its only totally secure cryptogram. Recruited from the vast reaches of the Navajo Reservation in Arizona and New Mexico, from solitary and traditional lives, the young Navajo men who made up the code talkers were present at some of the Pacific Theatre?s bloodiest battles. They spoke to each other in the Navajo language, relaying vital information between the front lines and headquarters. Their contribution was immeasurable, their bravery unquestionable. The photographer has recorded them as they are today, recalling their youth. Black-and-white photographic portraits of 75 survivors from the Navajo radio operators whose native tongue proved an unbreakable code to the Japanese during World War II. The introduction includes a few photographs from the period.
Introduction / Benis M. Frank -- Photographs -- Navajo clan names.
104993
Keywords: USA -- Marine Corps; 1939-1945; World War, 1939-1945 -- Cryptography; World War, 1939-1945 -- Indians -- Portraits; Navajo code talkers -- Portraits; Navajo Indians -- Portraits; Navajo language; United States -- Armed Forces -- Indians -- Portraits; Navajo-Sprache.